School in the hospital: reduce parents’ anxiety / Norazlin Abd Aziz, Nor Syamaliah Ngah and Azila Ayob - Abd Aziz, Norazlin; Ngah, Nor Syamaliah; Ayob, Azila (Universiti Teknologi MARA, Negeri Sembilan, 2023)
The Malaysian Ministry of Health and the Ministry of Education have jointly launched the School in the Hospital (SDH) program to prevent school dropouts caused by prolonged or frequent absences from school due to medical treatment. The readiness and aptitude of students with health conditions are the focus of the specialised and regulated learning facility in the hospital known as SDH. Learning at SDH is flexible and fun, and the teacher acts as a facilitator to help students follow the curriculum. In this way, human capital development can continue outside the confines of traditional educational processes. Currently, there are 15 SDHs throughout the country. In order to fulfil their social obligations, non-governmental organisations and companies have always given their attention and cooperation to the implementation of the SDH program. The donations are very helpful in implementing the planning of the programme.